Hubungan Kadar Ureum dan Kreatinin dengan Elektrolit Pada Penderita Gagal Ginjal Kronik - Iziana, Wafda Vivid; Widyantara, Aji Bagus; Solikah, Monika Putri (Innovative: Journal Of Social Science Research, 2024)
Chronic kidney failure is a progressive condition characterized by a decline in the glomerular filtration rate, which eventually affects electrolyte levels in the body. This imbalance often leads to serious complications in patients. This study aims to identify the relationship between urea and creatinine levels with electrolyte levels in patients suffering from chronic kidney failure. To achieve this, the research utilized a literature review method by gathering data from two main databases: PubMed and Google Scholar. The literature search was conducted by considering studies relevant within a specified time frame. The analysis of several reviewed journals revealed that urea levels in chronic kidney failure patients ranged from 122.5 to 165.7 mg/dL. Meanwhile, creatinine levels varied between 3.9 and 12.6 mg/dL. Additionally, sodium electrolyte levels showed an increase, ranging from 134.5 to 136.8 mmol/L. On the other hand, potassium levels ranged from 4.4 to 5.6 mmol/L, which remained within normal limits for some patients. Chloride levels were also relatively stable, with a range of 100 to 107.1 mmol/L. Based on the review of this literature, it is concluded that there is a significant increase in urea, creatinine, and sodium levels in patients with chronic kidney failure, while potassium and chloride levels tend to remain within normal ranges. Recommendations for future research include exploring other variables that may influence electrolytes and other biochemical parameters in patients with chronic kidney failure, in order to gain a more comprehensive understanding of this condition and its management.